Effect of Cognitive Biases on Investment Decision Making: A Case of Pokhara Valley, Nepal (Quest Journal of Management and Social Sciences, 2022)
Background: Behavioral finance deals with the study of psychological influences on investors and financial markets. Investors commonly perform investment analysis through fundamental and technical analysis. The behavior of the investment market originates from the principles of psychological decision-making that explains the reasons behind buying and selling stocks.  Objectives: This paper aims to examine the effect of cognitive biases on investment decisions in Pokhara Valley, Nepal. The effect of five cognitive biases, such as availability, anchoring, overconfidence, herd instinct, and regret aversion, is measured on rational investment decision-making. Methods: This study is based on primary data sources using non-probability (convenience method) sampling techniques. There are seven brokerage houses in Pokhara valley, and researchers selected 179 respondents involved in stock market investment. Both descriptive and inferential analyses were made to analyze the data. Results: The study discovers a link between irrationality in financial decision-making and availability, overconfidence, and herd instinct biases, but anchoring and regret aversion biases had no effect on irrational investment decisions. However, though all the biases have a positive relationship with an irrational investment decision, overconfidence bias has the highest impact. Regret aversion bias has the least impact on investment decisions in comparison to the other four biases. Conclusion: The investors and the policymakers should focus on finding the cognitive biases and various de-biasing methods to eradicate those biases throughout investment decision-making. The findings of this study have a number of implications for investors, brokers, and governments who aim to stimulate stock market investment.